Evaluation of the Number of Binding Sites in Proteins from Their Intrinsic Fluorescence: Limitations and Pitfalls - Lissi-Gervaso, E; Campos-Deramond, A; Campos-Deramond, A; Calderon-Espinoza, C; Calderon-Espinoza, C (2013)
Changes in the intrinsic protein fluorescence with the additive concentration provide one of the most employed methodologies for the evaluation of the binding constant and the number of binding sites. In the last years, more than 175 studies have been published where the double logarithmic plot shown below is used toward determining the number of equivalent binding sites (n). Log [(F° - F)/F] = log K + n log [Q0]. However, the value of n evaluated by this procedure is unrelated to the number of equivalent binding sites; rather it represents the stoichiometry of the binding step. The confusion on the meaning of n arises upon assuming that the binding process is represented by the forward and backward elementary steps shown below, implying that binding of the n solutes takes place simultaneously, i.e. there are no intermediate species. nQ + P ? QnP. The conclusion that n is unrelated to the number of equivalent binding sites is supported by the fact that in all the systems considered (99% of them) n values are close to one and much smaller than those obtained by ultrafiltration. It is then remarkable, the profusion of publications in peer-reviewed, specialized journals including a conceptual error that confuses Hill s coefficient and/or the stoichiometry of the binding step with the number of independent binding sites. Here, we discuss the origin of this common misconception and provide alternative methods to determine the number of binding sites. © 2013 The American Society of Photobiology.